Professional athletes and charitable foundations: an exploratory investigation. (1st January 2011) - Tainsky, Scott; Babiak, Kathy
Sport and philanthropy are becoming entwined. As professional athletes garner increasing attention beyond what they do on the field of play, a corresponding stakeholder expectation of athletes' charitable involvement has followed. By identifying trends in players who have private charities, we can evaluate the extent to which philanthropy promotes benefits to the player, team and league. Using the lenses of pro-social behaviour and corporate social responsibility, the purpose of this research is twofold. First, we provide an empirical analysis to profile athletes with charitable foundations, finding a connection between firms and athletes engaging in charitable behaviours. Second, we provide a theoretical framework for understanding professional athletes' connection to participate in socially responsible behaviour including the potential impact of their work on the firms they represent. Our regression analysis suggests older, higher paid athletes are more likely to create foundations and association with a charitable team also predicts athlete philanthropy.